THE EFFECT OF THE IMPLEMENTATION OF QUANTUM TEACHING STRATEGY IN TEACHING WRITING A DESCRIPTIVE TEXT - Fikri Asih Wigati (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2016)
The research was aimed to know the effect of Quantum Teaching Strategy (QTS) on the student’s performance of English Writing Skill in comparison to Conventional Teaching Strategy (CTS). The quantitative research was to measure the  effects of QTS on the Writing performance. The data was taken from an experimental research, involving 30 students in UNSIKA (Singaperbangsa Karawang University) in the English Education program. The 3rdsemester students were randomly selected. 15 students run learning activity with quantum learning method and 15 students studied in control group.  The experimental group got particular treatments related to quantum learning method. The treatment for the experimental group was practicing writing through experiencing the 5 steps of The control group was taught in conventional teaching strategy. Both groups pretest and post test to identify their performance on the writing skill improvement. The measurement for both groups was conducted at the same test. In term of quantitative approach, quasi experiment design was used to describe the different result of experimental group and control group. T-test was used to analyze the data to measure the effect of quantum teaching strategy in comparison to Conventional Teaching Strategy (CTS). By means of The T Test, the finding showed that QTS affected the performance of the students’ Writing skill. It is recommended for English Teacher to use QTS as alternative to improve quality of teaching.Keywords: Quantum Teaching Strategy, Writing